2010
DOI: 10.1159/000289200
|View full text |Cite
|
Sign up to set email alerts
|

T Cells as Sources and Targets of TNF: Implications for Immunity and Autoimmunity

Abstract: TNF is a pleiotropic cytokine produced by many cell types upon different stimuli and in various physiological and pathological conditions. In this review, we focus on the role of TNF in T cell responses as demonstrated by in vitro and in vivo observations in mice and humans. TNF has an impact on all aspects of T cell biology such as development in the thymus, peripheral homeostasis, primary antigenic responses, apoptosis, effector functions, memory cell formation and tolerance induction and maintenance. In mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 106 publications
1
32
0
Order By: Relevance
“…As D. sardus skin secretions do not contain the cationic ␣-helical hostdefense peptides that are produced in the skins of several other frog species [10,11], the system of adaptive immunity may be of particular importance in this animal. Pro-inflammatory cytokines function as immunostimulatory agents and several compounds that stimulate cytokine release are in clinical practice [7,25]. We suggest, therefore, that a possible role for frenatin 2D is activation of macrophages in frog skin to produce cytokines that stimulate the adaptive immune response to invading microorganisms.…”
Section: Discussionmentioning
confidence: 96%
“…As D. sardus skin secretions do not contain the cationic ␣-helical hostdefense peptides that are produced in the skins of several other frog species [10,11], the system of adaptive immunity may be of particular importance in this animal. Pro-inflammatory cytokines function as immunostimulatory agents and several compounds that stimulate cytokine release are in clinical practice [7,25]. We suggest, therefore, that a possible role for frenatin 2D is activation of macrophages in frog skin to produce cytokines that stimulate the adaptive immune response to invading microorganisms.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, in TNF-␣-deficient mice, transferred TNF-␣ ϩ/ϩ CD8 ϩ T cells were able to induce oviduct pathology that was intermediate between those of wildtype C57BL/6 mice and TNF-␣ Ϫ/Ϫ mice, suggesting that TNF-␣ production from both CD8 ϩ T cells and non-CD8 ϩ T cells may mediate chlamydial pathogenesis. TNF-␣ can be produced by a broad variety of cell types, including fibroblasts, macrophages, mast cells, and lymphocytes (4). TNF-␣ binds to two receptors, TNF-R1 and TNF-R2, and is known to activate at least three different signaling cascades (5,43): (i) NF-B signaling leading to very strong anti-apoptotic effects, (ii) JNK pathway leading to generally proapoptotic effects, and (iii) FIG.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent findings have demonstrated that the liver-damaging effects of TNF␣ in this disease model are largely mediated indirectly via the activation iNKT cells. [33][34][35] In addition, TNF␣ mediates an increased influx of circulating lymphocytes into the hepatic sinus and their subsequent local proliferation via blastoid formation, which further contributes to liver destruction. [33][34] The high expression levels of Toso in NKT cells and in activated cytotoxic T cells, together with a lack of Toso expression in hepatocytes therefore suggests the following scenario.…”
Section: Pathophysiologic Functions Of Tosomentioning
confidence: 99%
“…[33][34][35] In addition, TNF␣ mediates an increased influx of circulating lymphocytes into the hepatic sinus and their subsequent local proliferation via blastoid formation, which further contributes to liver destruction. [33][34] The high expression levels of Toso in NKT cells and in activated cytotoxic T cells, together with a lack of Toso expression in hepatocytes therefore suggests the following scenario. On TNF␣-engagement Toso Ϫ/Ϫ leukocytes are more likely to undergo apoptosis and only few potentially autodestructive immune cells get activated in Toso Ϫ/Ϫ mice.…”
Section: Pathophysiologic Functions Of Tosomentioning
confidence: 99%